Nutritional Intervention with Bacillus subtilis strain PB6 in Early Days, enhances Performance without affecting Carcass Characteristics of Broiler Chickens - Nabila Fathima; Rajendra Moorthy Rajendran; Ravichandran Mani; Srinivasan Balaji; Santosh Vyas (International Journal of Veterinary Science and Research - Peertechz Publications, 2022)
The objective of the study was to evaluate the combinational effect of Bacillus subtilis strain PB6 along with vitamins (V), minerals (M), and amino acids (A) on performance, growth, and carcass characteristics of broiler chickens during the early days and compare with commercially available combinations of V+A, and M+A without probiotics. An in vivo trial was conducted for a period of 35 days with day 1 Cobb 430 broiler chicks, randomly allotted to one control and four treatment groups namely T1 (PB6+VMA-1 g/L), T2 (PB6+VMA-2 g/L), T3 (V+A-1 mL/L) and T4 (M+A-2 mL/L) using a completely randomized design. Each group had 7 replicates and 12 birds per replicate. The performance parameters such as body weight (BW), and feed conversion ratio (FCR) were monitored throughout the trial. At the end of 7 days, BW was significantly higher for T2 (174.71 g) in comparison with T1 (173.99 g), T3 (174.41 g), T4 (173.39 g), and control (173.35 g, p < 0.05). However, no difference in FCR was observed (p > 0.05). Similarly, at the end of 35 days, T2 (1842.15 g) showed the highest BW compared to control (1818.36 g), T1 (1839.39 g), T3 (1833.20 g), and T4 (1816.73 g) and significantly least FCR (1.53, p < 0.05) in comparison with control (1.55), T1 (1.54), T3 (1.57) and T4 (1.56). At the end of 35 days, carcass characteristics such as carcass, breast meat, and organ yield were evaluated and no significant difference between the groups was observed (p > 0.05). The gut health of the birds was assessed by evaluating the dysbacteriosis and total mean lesion score at the end of 35 days and a score of less than one was observed for all the groups. Furthermore, return on investment (ROI) was analyzed and T1 showed an ROI of 2.21:1, followed by T2 which showed an ROI of 1.72:1, and no ROI was seen for T3 and T4. The results from this study suggest that supplementation of PB6 along with essential nutrients has a positive impact on the performance of broiler chickens, without affecting gut health and helps poultry producers for profitable farming.